Patterns of Dependency in Patron-Client Relations in the Coastal Community of Dawi-dawi Subdistrict, Pomalaa District, Kolaka Regency - Nur Azisyah Mukmin; Andy Budi Nofrianto; Asrani (CV. Literasi Indonesia, 2026)
The continuous growth of coastal populations increases the complexity of social and economic problems in fishing communities, particularly related to dependency on patron-client relationships. This study aims to analyze the pattern of dependency in patron-client relations within the fishing community of Dawi-dawi Subdistrict, Pomalaa District, Kolaka Regency. The research uses a qualitative approach with a descriptive design. Informants were selected purposively, consisting of fishermen as clients, fish dealers as patrons, and community leaders. Data were collected through in-depth interviews, observations, and documentation, and then analyzed through the stages of data reduction, data presentation, and conclusion drawing with triangulation techniques to ensure data validity. The results of the study show that patron-client relations are formed due to unequal access to capital, markets, and means of production. Fishermen’s dependency is reinforced through debt mechanisms, obligations to sell catches below market price, and informal socio-economic support from patrons. In the context of fluctuating income due to uncertain seasons and weather, patronage functions as an informal social safety net that fills the gap in access to formal financial institutions. However, this relationship also reproduces structural inequalities that limit the economic independence of fishermen. This study affirms that patron-client relations are not only an adaptive strategy but also a social structure that has the potential to hinder the empowerment of coastal communities. Therefore, strengthening formal institutions and community-based empowerment strategies are needed to reduce dependency and promote the independence of fishermen.